Effects of Different Doses of Quercetin on Apoptotic Markers and Liver Enzymes in Liver Injury Induced by Interferon Beta-1b (Betaferon) in Male Rats in Comparison with Silymarin - Noor Kamel Obead; Inam Sameh Arif; Huda jaber waheed (Iraqi Journal of Pharmaceutical Sciences)
The first disease-modifying drug for the treatment of multiple sclerosis (MS) was interferon beta 1b (IFN).this drug demonstrated efficacy in relapse MS, But There are many difficulties in treating multiple sclerosis, including the well-known side effect of betaferon(hepatotoxicity or liver injury), which present as brief, mild elevations in serum aminotransferase (ALT,AST) levels appear 3 to 12 months after starting treatment. A naturally occurring antioxidant is quercetin which act as anti-oxidant, anti-inflammatory agent , it also have antiviral, anticancer and cardiovascular   properties.The study aimed to investigate the apoptotic potential of betaferon on liver cells and to evaluate the hepatoprotective effect of the antioxidant quercetin , by downregulation of apoptotic biomarkers caspase 3 and caspase 9.The study was employed on 36 male rats for 17 days. rats were randomly  divided  into  six  groups  (6 rats  in  each  group) given daily doses given by Intraperitoneal route (i.p)as follow:Control group; (rats were administered distilled water),betaferon group or induction group ; (rats were administered Betaferon in a dose of 250 µ/kg for 16 days) ,treatment groups betaferon+ quercetin which divided into three subgroups according to the dose of quercetin (25,50,100mg/kg) ; (Rats were pretreated by a dose of 25,50,100mg/kg of quercetin suspension for 6 days then continue administering the same dose of quercetin plus betaferon 250µ/kg on day 7 for 10 days) .and the last group was Silymarin group; (rats were treated with 100 mg/kg of Silymarin suspension for 16 days).In the current study liver function enzymes such as alanine aminotransferase and aspartate aminotransferase also apoptotic markers which include caspase3 and caspase9 were measured.Betaferon significantly increased liver apoptotic markers caspase3 and caspase 9 also cause elevation in the liver enzymes(ALT,AST)compared to the control group. On the other side, quercetin  significantly reduce these biomarkers(caspase 3,caspase 9)also restoring liver enzymes to its normal level. Quercetin showed antioxidant,anti_inflammatory and anti_apoptotic effects on the liver tissue of rats that were pretreated with querctin before receiving the betaferon,suggesting it has a beneficial effects on minimizing liver injury or hepatotoxicity caused by betaferon.